Effect of Deep Breathing Relaxation and Progressive Muscle Relaxation on Blood Pressure - Hasim Asyari; Slamet Rohaedi; Marsono Marsono; Nafisah Itsna Hasni; Irma Darmawati (Jurnal Penelitian Pendidikan IPA, 2024)
Hypertension, characterized by diastolic pressure exceeding 90 mmHg and systolic pressure surpassing 140 mmHg, poses a significant health challenge often addressed through pharmacological antihypertensive therapy. This research endeavors to evaluate the impact of complementary interventions, specifically deep breathing relaxation and progressive muscle relaxation, on reducing blood pressure among hypertensive patients within the operational domain of the Kertasemaya Community Health Center in the Indramayu Regency in 2023. Adopting a Quasi-Experimental Design with a Pretest-Posttest and Control Group paradigm, the study engaged a cohort of 70 respondents stratified into intervention and control groups. The intervention group underwent a combined therapy of deep breathing relaxation and progressive muscle relaxation, followed by a meticulous post-test for final observations. Meanwhile, the control group underwent an initial blood pressure measurement (pre-test), a relaxation period of 15-30 minutes, and concluded with a post-test for final measurements. The study revealed a statistically significant influence (p=0.013) on average blood pressure within the intervention group compared to the control group. This disparity was observed both before and after the implementation of deep breathing relaxation and progressive muscle relaxation techniques among hypertensive respondents. These findings underscore the potential efficacy of non-pharmacological interventions in mitigating hypertension and enhancing patient well-being. The combination of deep breathing relaxation and progressive muscle relaxation emerges as a highly effective strategy in reducing blood pressure among hypertensive individuals. This integrative therapeutic approach showcases promising potential for promoting cardiovascular well-being, offering a valuable non-pharmacological avenue for hypertension management